Pengaruh Peran Gereja terhadap Pengembangan Potensi Generasi Muda Menurut Matius 25:14-30 di Gereja Bethel Indonesia Purwokerto City Walk - Yoshua Victor; Maria Titik Windarti (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
This study explores the influence of the church's role on the development of youth potential based on the text of Matthew 25:14-30 at Bethel Church Indonesia (GBI) Purwokerto City Walk. The study is confined to the Biblical study of Matthew 25:14-30, with research questions encompassing trends in youth potential development, the church's role, the church's influence on youth potential development, and dominant indicators of the church's role. Using a quantitative method, the study involves 100 congregants of GBI PCW, with data collected through questionnaires highlighting the church's role and youth potential development. The findings indicate a positive direction in youth potential development and the church's role, with the church significantly influencing by 26.8%, particularly as a center for mentoring. Recommendations include enhancing church programs and further analysis of unidentified factors. These efforts are expected to enhance the church's effectiveness in supporting holistic growth and development of the youth.